A Comparison of the Ideal Agrarian Reform Law to be Implemented in Indonesia - Darwin Ginting (Jurnal Wawasan Yuridika, 2022)
The purpose of this research is to examine the ideal agrarian reform program for Indonesia by conducting a comparison method with Japan, which is one of the countries in Asia that has been very successful in implementing agrarian reform. This research is descriptive research with a normative juridical research type, using secondary data, through legislative and comparative approaches. Data is collected through document studies and then analyzed qualitatively. The results of the research found similarities and differences between the two agrarian reform models. From these differences, it can be seen the advantages of Japanese agrarian reform that need to be adjusted to the need to improve Indonesia's agrarian reform, including compensation for excess land and absentee land that is used as the object of agrarian reform is given in the form of bonds; the agrarian reform team is independent; the government buys all excess land, the government provides a budget as needed.